FOOD HYGIENE PRACTICES AMONG FOOD HANDLERS IN SELECTED RESTAURANTS HAWLE WADAG DISTRICT IN BANADIR REGION MOGADISHU-SOMALIA - Hassan, Gallad Dahir; Hirsi, Dahir Ali; Ahmed, Hodo A/nor (Journal of Health, Medicine and Nursing, 2020)
Purpose: The aim of the study was to assess food hygiene practices among food handlers in restaurants located Hawle Wadag District in Banadir region Mogadishu-Somalia. Methods: This study was community based cross-sectional study and the data were collected from 30 cookers from 30 restaurants in Howlwadag District using 36 closed ended, administrated questionnaire between November and December 2019. Data were analyzed by using Statistical Package for Social Science (SPSS) version 20. Results: The findings indicated that two third of the respondents 20(66%) were illiterate and all the respondents of the study did not attend training course of food hygiene before they started work, they were not aware that the diseases could be transmitted through contaminated food. The study also indicated that the majority of the respondents 23(76%) reported they washed their hands only at the beginning of the day, which means more than two-third of the respondents reported that they only make hand washing when they start at the work. Food handlers in restaurants often use aprons to keep their clothes clean, but the study participants did not always use them even when aprons were available. The study also indicated that 25(83%) of the respondents had no medical fitness card and the owners of the restaurant didn't care about the health of food handlers whether they were ill-health or not which made it possible of food handlers to be carriers of communicable disease and the disease could be transmitted to other people, Unique Contribution to Theory, Practice and Policy: Public Health authorities need to ensure that food handlers receive medical screening on regular bases, and they should establish and enforces rules and regulations dealing with hygienic practices in the handling of food. Food handlers need basic training in cooking and food hygiene. Restaurant managers will constantly monitor the hygienic condition. Food handlers give personal protective equipment to prevent any problems of food handlers themselves and the community such as diseases transmission such Hepatitis B virus, typhoid and etc. Requirements for recruiting food handlers should add medical examination prove or health ID in the last six months.